A case of occlusal reconstruction using dental implants after Le Fort I osteotomy simultaneously with maxillary sinus floor augmentation: Require to preserve the maxillary sinus membrane?. Issue 5 (September 2022) - Kanno, Yuki; Saijo, Hideto; Mori, Yoshiyuki; Hoshi, Kazuto; Chikazu, Daichi; Kawase-Koga, Yoko
Abstract: In cases of multiple missing teeth with severe jaw deformity, dental implant pretreatments such as bone grafts are generally performed after orthognathic surgery. Bone grafting to the maxillary sinus floor at the same time as Le Fort I osteotomy has previously been reported; however, few of these studies were conducted in Asia-Pacific. Furthermore, two conflicting theories have been reported concerning the preservation of the maxillary sinus membrane. We report a case of occlusal reconstruction using dental implants after Le Fort I osteotomy conducted simultaneously with sinus floor augmentation. A 44-year-old man was referred to our department with chief complaints of facial deformity and occlusal malfunction. He had skeletal mandibular prognathism with facial asymmetry, right upper jaw deformity after fracture healing, multiple missing teeth, and bilateral maxillary alveolar bone atrophy. As the first-step surgery, a Le Fort I osteotomy and bilateral sagittal split ramus osteotomy were performed under general anesthesia at the same time as maxillary sinus floor augmentation. We attempted to preserve the sinus mucosa; however, damage to the right sinus membrane was unavoidable. Nevertheless, we performed bone grafting while ensuring secure fixation. Subsequently, there was no difference in the resorption of the grafted bone between the two sides. In the second-step surgery, bilateral maxillary dental implants were placed under local anesthesia．A few months later, one implant was lost during the prosthetic treatment period, ultimately the patient expressed satisfaction with the occlusal reconstruction and improved facial appearance. Furthermore, we succeeded in dramatically shortening the treatment period.